KONTRIBUSI KOPERASI DAN UMKM DALAM MENDORONG PERTUMBUHAN EKONOMI INDONESIA - Sabrina Arsy Wijaya; Halimatus Sa’diyah; Wardatun Nikmah; Nurus Sobakh (CV. Denasya Smart Publisher, 2026)
Post-COVID-19 has increasingly highlighted the strategic role of the real sector, particularly cooperativesand Micro, Small, and Medium Enterprises (MSMEs), as the keyy drivers of national economic recoveryand inclusion. However, fundamental questions remain regarding the extent of their roles andcontributions, as well as the factors that support their success in driving economic growth amid postpandemicdynamics. This study examines the role of cooperatives in Indonesia's economic growth, examinethe contribution of MSMEs to the national economy, and identify the supporting factors behind theirsuccess. The study employs only a descriptive qualitative method with a literature review approach,examining various scientific sources including books, journals, and relevant articles. The results indicatethat MSMEs contribute approximately 61% to the GDP and absorb nearly 97% of the workforce, whilecooperatives play a role through providing access to capital, business services, and equitable distributionof business surplus to members. Key supporting factors include government policy support, access tofinancing, human resource development, and the adoption of digital technology. This study suggests thatthe synergy between cooperatives and MSMEs, supported by appropriate policy interventions anddigitalization, has the potential to make both sectors inclusive, competitive, and sustainable drivers ofIndonesia's economic growth.